La perífrasis verbal ir a + infinitivo en las obras narrativas de Gabriel García Márquez - Markič, Jasmina (Vestnik za tuje jezike, 2015)
This article deals with ir a + infinitive, one of the most frequent verbal periphrases in Spanish with temporal, aspectual and modal values. It presents the analysis of narrative texts written by the Colombian writer Gabriel García Márquez and emphasizes the expression of aspectual values of imminence of the event and the expression of future with the auxiliary verb in present replacing the simple future tense in Colombian Spanish corroborating, thus, the fact that in contemporary American Spanish the expression of futurity is in the process of transfer from a synthetic to an analytic form. However, these aspectual and temporal values are not always alone, frequently they merge with other mainly modal values which confer to this periphrasis additional expressive and stylistic uses.
Keywords: García Márquez, Gabriel, 1928-2014; Spanish; španščina; Kolumbija; glagolska perifraza; časovnost; aspektualnost; modalnost; prihodnjik; future tense